Diaphragm ultrasound in critically ill patients - Khasne, Ruchira (Journal of Nepalese Society of Critical Care Medicine, 2025)
Diaphragm ultrasound (DUS) is a rapidly evolving and useful modality. Diaphragmatic dysfunction (DD) is common in critically ill patients and is associated with significant adverse outcomes such as need of intubation, prolonged mechanical ventilation, weaning failures, and mortality. Most commonly used indices in DUS are diaphragmatic excursion (DE) and diaphragmatic thickness fraction (DTF). As positive pressure ventilation affects these indices, so DUS should ideally done on spontaneously breathing patients. DE and DTF can be used to diagnose DD and to predict weaning outcome. Recent expert consensus has proposed cut off values for identification of diaphragmatic weakness and atrophy in critically ill patients. While performing DUS, it is recommended to scan the paradiaphragmatic areas to look for collapse/consolidation of the lungs, pleural effusion and any subdiaphragmatic pathology. As DUS is still in evolution, well designed randomized controlled trials are required to standardize the cut off values and to define the role of DUS for improving patient outcome.